Pengembangan Model Aquaponik-Hidroponik Berbasis IoT untuk Optimalisasi Pengelolaan Limbah Kolam Lele dan Peningkatan Produktivitas Pokdakan Tani Mandiri - Feka, Wolfhardus; Matoneng, Ody Wolfrit; Gelu, Leonard Peter; Keraf , Fransiskus Markus Pereto (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to address the issues of limited resources, low productivity, and weak managerial capacity of Mandiri Farmer Groups in the border region of Indonesia-Timor Leste. The proposed solution is the implementation of an aquaponic-hydroponic model based on the Internet of Things (IoT), which is integrated with business management training, digital record-keeping, and marketing strategies. The implementation methods include observation and problem identification, planning, training and mentoring, to evaluation of results. The results show an increase in horticultural productivity of 45% per cycle, water use efficiency reaching 48%, and an increase in product sales volume of about 31%. The application of IoT sensors also reduced fish mortality rates by up to 20% and facilitated monitoring of water quality. In addition to technical impacts, this activity enhances the financial literacy of group members and expands market access through digital marketing. The strength of the program lies in the appropriate and easy-to-operate technology, although challenges are still encountered in the initial adaptation to using digital applications. Overall, this activity has successfully created a sustainable, environmentally friendly technology-based empowerment model that can be replicated in other community groups in border areas.